(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Employee engagement has been termed as one of the major tools of Human resource management which ensures Job satisfaction and synchronizes the workforce to collectively strive towards the achievement of organizational objectives. The Covid-19 pandemic however changed the implementation and practices of several personnel management tools. The remote working/work from home culture has reduced the impact of traditional mechanisms and has given way to innovations that can be deemed suitable for the “new normal”. This paper attempts to analyze the new 5 C model propagated by several Human resource management practitioners. The assistance of existing literature and investigative articles has been taken while formulating this paper. This paper is of immense importance to scholars/ academicians/professionals working in the field of Human resource or personnel management